Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1590/s0104-66322005000400005
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of penicillin G acylase by immobilization on glutaraldehyde-activated chitosan

Abstract: -The objective of this work was to study enzyme immobilization on chitosan activated with glutaraldehyde, aiming to produce a cheap biocatalyst. Two different immobilization strategies were studied: one-point and multipoint covalent attachment to the solid matrix. The multipoint covalent attachment derivative had an 82% immobilization yield. It was 4.9-fold more stable than the free enzyme at 50°C and 4.5-fold more stable than soluble enzyme at pH 10.0. The one-point derivative had an 85% immobilization yield.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 13 publications
(19 reference statements)
1
40
0
6
Order By: Relevance
“…Different glutaraldehyde concentrations ranging from 0.25-2% w/v were tested for immobilization of 89L; resin activation was carried out in phosphate buffer (50 mM, pH 7) with immobilization ratio of 1:1, enzyme loading 4mg/ml of resin at 25°C for 16 hrs. It was observed that, enzyme binding increased linearly with glutaraldehyde concentration, but proteolytic activity of immobilized preparation showed initial increase followed by a slight decrease at higher concentrations ( Figure 5), similar trend was observed when acylase was immobilized at various glutaraldehyde concentrations [41]. At 1% glutaraldehyde concentration, highest proteolytic activity was observed without compromising enzyme binding.…”
Section: Variation Of Glutaraldehyde Concentration For Activationsupporting
confidence: 68%
See 1 more Smart Citation
“…Different glutaraldehyde concentrations ranging from 0.25-2% w/v were tested for immobilization of 89L; resin activation was carried out in phosphate buffer (50 mM, pH 7) with immobilization ratio of 1:1, enzyme loading 4mg/ml of resin at 25°C for 16 hrs. It was observed that, enzyme binding increased linearly with glutaraldehyde concentration, but proteolytic activity of immobilized preparation showed initial increase followed by a slight decrease at higher concentrations ( Figure 5), similar trend was observed when acylase was immobilized at various glutaraldehyde concentrations [41]. At 1% glutaraldehyde concentration, highest proteolytic activity was observed without compromising enzyme binding.…”
Section: Variation Of Glutaraldehyde Concentration For Activationsupporting
confidence: 68%
“…At low glutaraldehyde concentration, all amine groups of support matrix remain unutilized; while high glutaraldehyde concentrations lead to multi point attachment of enzyme. Suitable glutaraldehyde concentration varies with protease being used 1% for mungbean thiol protease [32], 5% for acylase [41] while 2% for papain [42]. Hence, there is need to determine suitable glutaraldehyde concentration, where, higher hydrolytic activity is obtained with minimal enzyme load.…”
Section: Variation Of Glutaraldehyde Concentration For Activationmentioning
confidence: 99%
“…In a study performed by Kamburov et al (2011) on covalent immobilization of trypsin on chitosan macrobeads, immobilization led to the increase of the enzyme heat resistance. Adriano et al (2005) indicated that the immobilization of penicillin G on chitosan activated by glutaraldehyde can increase the stability of the enzyme 4.9-fold at 50 °C and 4.5-fold at pH 10.0. Kuo et al (2012) immobilized lipase on chitosan-coated Fe 3 O 4 nanoparticles activated with EDC as coupling agent.…”
Section: Effect Of Temperature On Enzyme Stabilitymentioning
confidence: 99%
“…A wide variety of immobilization techniques may be employed in order to reduce these operational problems and improve the catalytic activity and ability of these enzymes. It is possible to vary the nature of the immobilized derivative in order to design efficient biocatalytic processes (Adriano et al, 2005;Mohy Eldin et al, 2000). Vol.…”
Section: Introductionmentioning
confidence: 99%